As given three years ago, the age of boy = y
∴ the present age of the boy = (y + 3) years.
⇒ The age of boy 2 years ago = (y-2) years.
Hence, it is true.
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation